Postoperative analgesic effects of epidural administration of neostigmine alone or in combination with morphine in ovariohysterectomized dogs - Marucio, Rodrigo L. [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Teixeira Neto, Francisco José [UNESP]; Minto, Bruno W. [UNESP]; Hatschbach, Eduardo [UNESP] (Amer Veterinary Medical Assoc, 2008)
Objective-To evaluate analgesic effects of epidurally administered neostigmine alone or in combination with morphine in dogs after ovariohysterectomy.Animals-40 healthy bitches.Procedures-After acepromazine premedication, anesthesia was induced. Dogs randomly received 1 of the following 4 epidural treatments 30 minutes before ovariohysterectomy (n = 10/group): saline (0.9% NaCl) solution (control), morphine (0.1 mg/kg), neostigmine (10 pg/kg), or morphine-neostigmine (0.1 mg/kg and 10 pg/kg, respectively). Analgesia was assessed for 24 hours after surgery by use of a visual analogue.scale (VAS; scale of 0 to 10) or numeric descriptive scale (NDS; scale of 0 to 24) and by the need for supplemental analgesia (morphine [0.5 mg/kg, IM] administered when VAS was >= 4 or NDS was >= 8).Results-Significantly more control dogs (n = 8) received supplemental analgesia, compared with the number of neostigmine-treated dogs (1); no dogs in the remaining groups received supplemental analgesia. Compared with values for the control dogs, the NDS scores were lower for morphine-neostigmine-treated dogs (from 2 to 6 hours and at 12 hours) and for morphine-treated dogs (all time points). The NDS scores were lower for morphine-treated dogs at 3, 12, and 24 hours, compared with values for neostigmine-treated dogs. The VAS was less sensitive than the NDS for detecting differences among groups.Conclusions and Clinical Relevance-Epidurally administered neostigmine reduced the use of supplemental analgesia after ovariohysterectorny in dogs. However, analgesic effects were less pronounced than for epidurally administered morphine or morphine-neostigmine. Adding neostigmine to epidurally administered morphine did not potentiate opioid-induced analgesia.